D is for dahl: a gloriumptious a-z guide to the world of roald dahl - Blake, Quentin; Cooling, Wendy (Puffin London, 2005)
Alphabetically arranged book full of amazing top-secret facts about Roald Dahl, Willy Wonka, The BFG, Charlie Bucket, beards and lots more